Enduring personality changes in patients living at home and challenges for community nursing - Maček, Bernarda (Obzornik zdravstvene nege, 2015)
Introduction: Personality and behaviour disorders include enduring personality changes which cannot be attributed to brain injury or disease. Traumatic experiences can cause personality vulnerability. The research aimed to determine the characteristic enduring personality changes, the risk factors and the quality of life of patients living in their home environment. Methods: The field research is based on a quantitative method. The data were gathered through a structured questionnaire. The sample consisted n = 606 of patients (18.56 %) from the Central Slovenia region, aged between 20 and 92 years. The data were processed using descriptive statistics, the %2 test, group classification and discriminant analysis. Results: The enduring personality changes are present in 9 % (n = 53) of the patients who tend to be older, with lesser educational attainment. Only a quarter of the enduring personality changes patients (n = 10) are receiving psychiatric treatment. Among the groups of patients with or without enduring personality changes statistically significant differences have been observed in relation to their past experiences with a traumatic event (p < 0.001), level of independence in the performance of the activities of daily living (p < 0.001), incidence rate of chronic pain (p = 0.002), social integration (p = 0.016), suicidal thoughts (p < 0.001) and incidence rate of comorbidity of somatic illnesses and psychological disorders (p < 0.001). Discussion and conclusion: Results of the study point to the share of enduring personality changes patients living at home in which the condition remains largely unrecognized, untreated and shadowed by other mental and physical health issues. Community nurses play a crucial role in timely recognition and detection of the changes and the patients' referral to multidisciplinary treatment. A national research project conducted by community nurses is needed to highlight the prevalence, treatment and good practice in the delivery of pertinent services.
Keywords: community nursing; osebnostne spremembe; pacienti; patients; patronažna zdravstvena nega; personality changes; traumatic experiences; travmatične izkušnje